Development of new strategy combining heat treatment and phage cocktail for post-contamination prevention. (July 2021) - Park, Haejoon; Kim, Jinwoo; Kim, Minsik; Park, Yerin; Ryu, Sangryeol
Graphical abstract: Highlights: Thermostable phages were isolated by applying a heating-step to phage isolation. Thermostable phage cocktail was constructed to kill Salmonella strains effectively. Phage cocktail was combined with LTLT pasteurization and hard scalding method. Phage cocktail prevents Salmonella contamination in milk and chicken meat model. Abstract: Heat treatment is an effective method for ensuring food safety and quality by controlling microbial contamination. However, food poisoning outbreaks have continuously occurred in heat-treated products due to improper thermal treatment and/or post-contamination of foodborne pathogens. This study proposes a novel strategy combining thermostable bacteriophages with thermal processing of food production plants to control foodborne pathogens and even bacterial contamination. Typically, bacteriophages' susceptibility to heat is a major challenge to their application with thermal processing, we isolated thermostable bacteriophages by a modified isolation method of applying heat to samples and characterized the thermostable bacteriophages. Furthermore, we optimized the bacteriophage cocktail components to expand the controllable host range and reduce the risk of bacteriophage resistance development. Finally, we verified this antibacterial strategy by combining heat treatment with thermostable bacteriophages in model systems, including milk and chicken breast. After the phage cocktail and heat treatment, we artificially contaminated the food products to mimic the post-contamination event. Surprisingly, the remaining bacteriophages that withstood heat treatment significantly reduced the number of post-contaminated Salmonella . Altogether, thermostable phages could be applied as complementary tools to control post-contamination after thermal processing of food products.